Morality through Metaphor: a Cross-Linguistic Analysis of Political Discourse - Arcimavičienė, Liudmila (Kalbotyra, 2008)
For centuries the on-going debate of the relationship between morality and politics has resulted in the division of such fundamental concepts as the right and the good, justice and equality, democracy and liberty etc (Paul, Miller & Paul 2004, 56).The main issue of this scholarly debate has been centred round the distinction between moral and pragmatic politics. For example, Aristotelian claim is based on the assumption that the proper aim of politics is a moral virtue, whereby good and morally right actions such as care, empathy and emotions dominate (ibid., p. 12). [...]